Menggali Makna di Balik Karya Mural: Analisis Komunikasi Visual Gate 17 Persebaya dalam Menyampaikan Pesan kepada Suporter - Dhimas Rizky Putra Aditya; Nurannafi Farni Syam Maella (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study explores the role of visual communication by Persebaya supporters' communities, particularly Gate 17, in conveying messages to Persebaya supporters and the general public. It explores how symbols and visual elements in murals, banners and digital graphics are used as a means of expressing group identity, solidarity and loyalty. The study also examined the power of visual communication in shaping supporters' community narratives and their engagement with the club. The study employed a qualitative approach using interviews and observational methods to understand the meanings embedded in these visuals and how these elements resonate with supporters' identity and solidarity. In addition to being a medium for expressing support, the images also serve as a means of social commentary and collective action, fostering a sense of belonging among supporters. A literature review and analysis of visual communication theory are added to strengthen the theoretical basis of this research, providing insights into the dynamics of fan culture as well as the power of visual communication in a sporting context.